epuasan dan Intensi Merekomendasikan Salah Satu Perguruan Tinggi Dengan Belajar Daring Saat Pandemi Covid-19 - Liza Agustina Maureen Nelloh (Fakultas Ekonomi Universitas Islam 45, 2020)
The Covid-19 phenomenon hit the Higher Education sector which gathered all the institutions in Jakarta to implement an online learning system. This means a significant change from face-to-face learning to become learning from home. However, during this pandemic, there has been little evidence about existing studies that focus on online learning toward student satisfaction and Word of Mouth (WOM) intentions about Private Higher Education in Jakarta. To test the hypotheses, this study uses SEM-PLS with SmartPLS ver.3.2.8 of 60 students. The results show that service quality of online learning is significantly and positively effect on student satisfaction, and student satisfaction will cause positive WOM Intention. In conclusion, this study accepts all proposed hypotheses expected for IPMI International Business School in Jakarta. Therefore, during this Covid-19 outbreak, it is hoped that it can continue to improve the service quality of online learning that causes satisfaction and build positive WOM Intention among students in the Higher Education Sector.